LAND GRABBING DAN POTENSI INTERNAL DISPLACEMENT PERSONS (IDP) DALAM MERAUKE INTEGRATED FOOD AND ENERGY ESTATE (MIFEE) DI PAPUA - Amin Tohari (BHUMI: Jurnal Agraria dan Pertanahan, 2013)
This article discussed the possible impact of land grabbing practice toward the emergence of internal displacementperson taken a close look to MIFEE project in papua. employed the concept of acumulation by dispossesion, it was found that themajor scale farming development kept a serious impact toward the emergence of internal displacement person. they are oneswhose land, forest and other aource of living had been taken away. The MIFEE had cause a socio-cultural gap between farmingmechanism and mode of production of the local people, a massice demographical change, economic polarisation, power politicsmarginalization. with a big number of problems in IDP as a result of dispossesion practice, the IDP is directed toward group thatgot an effect of development expansion rather than those who suffer from disaster. in the context of human right, the MIFEE wasa great potention for the occurance of a violation toward the local people’s right.Keywords: Land Grabbing, Internal Displacement Persons, Accumulation, MIFFEE